El conde D. Enrique Manuel (c.1343-1414) y las relaciones cortesanas luso-castellanas en tiempos de crisis dinásticas - César Olivera Serrano (Medievalista)
This article analyzes the biographical data of Count Enrique Manuel, son of the famous writer Don Juan Manuel, from various points of view. On the one hand, his kinship relations with other descendants of Don Juan Manuel are explained, especially with the kings of Portugal, Castile and Aragon. This close family relationship allows us to understand a second level of analysis: his political leadership during the reigns of Fernando I of Portugal and Juan I of Castile. In those years, a marriage alliance and a succession agreement were prepared that finally failed with the triumph of João I de Avis. Thirdly, the breakdown of his own family is studied, since one of his daughters remained in Portugal and the rest of the children went into exile in Castile. Finally, the religious and symbolic messages used by the Manuel lineage at the end of the 14th century are analyzed within the context of the Portuguese-Castilian rivalry.